Cultural Plurality and the Challenges of Minority Education in Indonesia: A Multicultural Study - Masnun Baiti; Karoma Burlian; Abdullah Idi; Habibur Rachman; Sukirman Sukirman; Mualimin Mualimin (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2026)
Indonesia is known as a diverse nation with a wealth of cultures, ethnicities, religions, and languages. This cultural plurality is both a strength and a challenge in realizing education that is fair and inclusive, especially for minority groups. This article examines the relationship between cultural plurality and minority education from a multicultural perspective, highlighting how the national education system addresses the complexities of such diversity. The research method uses a literature study with a qualitative approach. Data collection techniques involve reading and drawing conclusions from various literature sources, including books or relevant articles. Data analysis techniques include inventorying, categorizing, and analyzing research data. The study results indicate that education in Indonesia still faces challenges in terms of equal access, cultural representation, and multicultural teacher competencies. Therefore, a humanistic educational approach that is culturally just and sensitive to local values is needed so that plurality becomes an integrative strength, rather than a source of exclusion.